(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
Staphylococcus aureus is one of the world’s most frequent pathogens that responsible for a wide range of infectious diseases. As plasminogen is converted into the active fibrinolytic enzyme, plasmin by staphylokinase, a staphylococcal protein Staphylokinase is also produced by S. aureus bacteria that infect people. Antibiotic-resistant bacteria are blocked from invading tissues by Sak achieve’s capacity to form complexes of plasminogen activating complexes with plasmin as well as with plasmin. As a result of staphylokinase’s tiny size, it also acts as an immunomodulator that is represented by an increase in IL-10 blood level (an anti-inflammatory cytokine) and a decrease in IL-4 serum level, which is associated with a reduction in the development of hypersensitivity. Both beneficial and detrimental effects can be achieved by immunomodulation. Immunomodulators abruptly modify informational molecules, like as cytokines, to affect the immune system’s activity. If streptokinase is administered regularly, it can cause allergic reactions and the formation of anti-streptokinase antibodies